HPF1 remodels the active site of PARP1 to enable the serine ADP-ribosylation of histones - Fa-Hui Sun (Nature Portfolio, 2021)
Once DNA breaks occur, poly(ADP-ribose) polymerase 1 (PARP1) ADP-ribosylates itself and other DNA repair factors to initiate the repair process. Here, the authors resolve the crystal structures of mouse and human HPF1, and human HPF1/PARP1 complex proving insights into PARP1 regulation.